La prima parte del "decennio di sviluppo": sviluppo, commercio e bilancia dei pagamenti dei paesi arretrati (The first half of the development decade: growth, trade and the balance of payments of the developing countries, 1960-65) - B. BALASSA (Moneta e Credito, 2014)
The developing countries approached the Development Decade - the period 1960-1970 - with great expectations. While export prospects were viewed with some pessimism, a considerable increase in the rate of economic growth was forecast. The present work uses data from the first half of the sixties in order to evaluate the extent to which these projections have been realised. The author considers the growth performance of the developing countries, increases in their exports and in the inflow of foreign capital, the use of foreign exchange earnings, the main influences affecting their economic growth, and the prospers for the second half of the Development Decade.